2017
DOI: 10.1002/dc.23641
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis and inflammatory response showed association with severity of cervical neoplasia in HPV‐positive women

Abstract: Vaginal infections may affect susceptibility to and clearance of human papillomavirus (HPV) infection and chronic inflammation has been linked to carcinogenesis. This study aimed to evaluate the association between bacterial vaginosis (BV) and inflammatory response (IR) with the severity of cervical neoplasia in HPV-infected women. HPV DNA was amplified using PGMY09/11 primers and genotyping was performed using a reverse line blot hybridization assay in 211 cervical samples from women submitted to excision of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…Confronting these results, Castro-Sobrinho et al, 28 evaluating cervical smears of HPV-infected women, found that Gardnerella vaginalis was the most frequent microorganism in smears with invasive carcinoma (18.2%) and HSIL (45.6%), concluding that bacterial vaginosis, may be associated with the severity of cervical neoplasia.…”
Section: Discussionmentioning
confidence: 96%
“…Confronting these results, Castro-Sobrinho et al, 28 evaluating cervical smears of HPV-infected women, found that Gardnerella vaginalis was the most frequent microorganism in smears with invasive carcinoma (18.2%) and HSIL (45.6%), concluding that bacterial vaginosis, may be associated with the severity of cervical neoplasia.…”
Section: Discussionmentioning
confidence: 96%
“…A considerable decrease in triglycerides concentrations was also seen following the supplementation of 600 mg/day magnesium as magnesium oxide for 8 weeks among people with T2DM [26]. Moreover, vitamin E and omega-3 fatty acids co-supplementation for 12 weeks to women with PCOS significantly improved lipid profiles [27]. In an animal study, vitamin E supplementation for 20 weeks reduced serum levels of triglycerides and VLDL-cholesterol, but did not affect other lipid profiles [28].…”
Section: Discussionmentioning
confidence: 99%
“…Lysyl hydroxylase (LH) is a protein encoded by procollage-lysine 2-oxoglutarate 5-dioxygenase (PLOD), which is a key enzyme mediating collagen-mediated oxygenase. PLOD gene families can be divided into three subtypes PLOD1, PLOD2, PLOD3, each subtype of the corresponding lysine hydroxylase gene encoding, the family belongs to 2-keto glutaric acid dependent two-plus oxygen members of the family of enzymes, with qi acid hydroxylase activity ( Shao et al, 2018 ), can be in Fe 2+ and 2 - keto glutaric acid is formed under the condition of homologous dimers, catalytic single former collagen lysine hydroxyl, lysine hydroxylation of collagen can be cross linked after secrete extracellular form stable structure of hydroxyl lysine pyridine chain ( Maria de Castro-Sobrinho et al, 2017 ). When the expression of PLOD2 is significantly increased in cells, the generation of hydroxylysine pyridine chain is increased, which will lead to excessive deposition of collagen fiber, damage of ECM structure, and further cause tumor progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%